Neutrosophic cubic Heronian mean operators with applications in multiple attribute group decision-making using cosine similarity functions. (September 2019) - Gulistan, Muhammad; Mohammad, Mutaz; Karaaslan, Faruk; Kadry, Seifedine; Khan, Salma; Wahab, Hafiz Abdul
This article introduces the concept of Heronian mean operators, geometric Heronian mean operators, neutrosophic cubic number–improved generalized weighted Heronian mean operators, neutrosophic cubic number–improved generalized weighted geometric Heronian mean operators. These operators actually generalize the operators of fuzzy sets, cubic sets, and neutrosophic sets. We investigate the average weighted operator on neutrosophic cubic sets and weighted geometric operator on neutrosophic cubic sets to aggregate the neutrosophic cubic information. After this, based on average weighted and geometric weighted and cosine similarity function in neutrosophic cubic sets, we developed a multiple attribute group decision-making method. Finally, we give a mathematical example to illustrate the usefulness and application of the proposed method.